PROSPECTIVE WAYS OF USING CLOUD-BASED SYSTEMS OF OPEN SCIENCE IN THE PROCESS OF TEACHERS OF NATURAL-MATHEMATICAL SUBJECTS TRAINING - Shyshkina, Mariya (Physical and Mathematical Education, 2023)
The work describes promising ways of introducing cloud-oriented systems of open science in the process of training and professional development of teachers of natural and mathematical subjects. Formulation of the problem. The scientific and methodological study and development of the methodology for using cloud-based open science systems in the process of training and professional development of teachers is aimed at increasing the level of their ICT competence, improving the skills of mastering the most modern ICT. Materials and methods. To achieve the goal of the work, general scientific methods were used: a) theoretical - analysis of scientific and methodological, psychological and pedagogical literature on the problem of research; generalization of domestic and foreign experience; theoretical analysis, systematization and generalization of scientific facts and patterns b) empirical - conversations with participants in the educational and scientific environment; pedagogical observations; questioning; testing.Findings. The paper substantiates that methodically balanced and expedient introduction of cloud-oriented systems of open science in the process of training and professional development of teachers will contribute to improving the level of organization of the educational process, improving its quality through the use of the most modern ICT, more active use of innovative forms, tools and technologies in the process of teacher training; improving their ICT competence. Conclusions. The introduction of cloud-based open science systems in the process of teacher training is a methodically expedient direction for improving the scientific education of teachers, this will contribute to the wider introduction of relevant educational content and the most modern technologies in the learning process. Promising ways of their implementation are such as: supporting group work and project-oriented learning; storage, processing, presentation and visualization of data in the process of scientific and scientific-educational research; big data processing; solving various special research tasks, both in the individual and collective mode.
Keywords: cloud services; open science; professional development; teachers